Hubungan Usia Dan Jenis Pekerjaan Terhadap Aktivitas Sehari-Hari Penderita Osteoartritis - Gus Prasetyo Hadi, Henda; Yani, Fitri; Risty Wardhani, Riska (CV RIFAINSTITUT, 2023)
A person's health has various levels, some are very weak so they easily experience health problems, but there are also those who are strong so they can tolerate it so they don't easily suffer health problems. So the relationship between age and increasing age causes the prevalence of OA to increase. Furthermore, there are also work relationships that use joints or rely on joints with very heavy loads, even more than the weight that our joints can bear. Objective: The aim of this research is to determine the relationship between age and type of work on the daily activities of osteoarthritis sufferers. Research Method: This correlative descriptive uses a cross sectional approach. The population in this study were osteoarthritis sufferers aged 55-70 years who were at the Bhayangkara DIY POLDA Hospital in 2023 totaling 49 patients. Data were collected using total sampling with a sample size of 33 respondents. Results: The results of the analysis using the chi square test showed a ρ-value of 0.126 p>0.05, with no relationship between age and daily activities of osteoarthritis sufferers shown, which means the hypothesis was rejected. Meanwhile, for the relationship between type of work and daily activities of osteoarthritis sufferers, the value of ρ 0.032 p>0.05. There is a relationship between the type of work and the daily activities of osteoarthritis sufferers. Conclusion: There is no relationship between age and the daily activities of osteoarthritis sufferers and the relationship between the two is very weak. Meanwhile, there is a significant relationship between the type of work and the daily activities of osteoarthritis sufferers and the relationship between the two is very strong. Suggestion: For future researchers, it is hoped that they will explain the relationship between age and type of work on the daily activities of osteoarthritis sufferers in detail so that it is clearer, and can also add variables to be studied to make it more complete.